SIG - metodologia - adequação ambiental em propriedades rurais em mananciais de abastecimento público: conseqüências socioenômicas - Paz, César Roberto Silva (2010)
The research proposes methodology applied to an integrated management of natural resources having the water as the main axis on a prioritary territorial unit, the micro-watershed Rio Sarandi, located in the Southwest of Paraná, whose 592 rural properties have been delimitated according to its original asymmetry, size variation, measured area of 18,45 Ha, inadequate infrastructure and with the intense use of soil, especially in areas of wavy smooth relief, essential to the regional social economical development. The research has been based on geoprocessing techniques and the application of a Geographic Information System (GIS) on a manantial with an area of 11.690 Ha, whose hydrography is born in Ampere city, supplies with water the urban population of Realeza and Santa Izabel do Oeste cities, where it has its largest/widest surface. It includes in the GIS an economical evaluation proposal based on the main and most vulnerable production systems, grains, milk, silk worm production and tobacco, involving 382 family agriculturalists. It has enabled the elaboration of an environmental study method with emphasis on the use of soil and water, generating thematic maps, current and precise information as well as simulations and diverse results about the anthropic action in the watershed, among which, the constatation of the existence of 55,6 % for riparian area and 46,8% of legal reservation necessary to the solution of the environmental passive. The reduction impact on agricultural operational income considering the useful area surface of rural properties, is from 4% to 13% in the implementation of the Permanent Preservation Area, with the possibility of compensation through the improvement of management and technological integration, although with a fall from 18% to 31% for the legislation fulfillment with the incorporation of Legal Reserve, depending on the activity, a fact that demonstrates the necessity of more debates regarding economical alternatives, which is a cause of unease and insecurity over the future for the citizens due to the dimension of these consequences. The result of the study has generated abundant educative content, qualitative and quantitative input for managers, public and private institutions, and for the community, contributing to the technical strategy and to the objective of the Integrated Environmental Management Program in Watersheds, that has recently been implemented by the Parana State Government.